2010
DOI: 10.1002/ejoc.200901150
|View full text |Cite
|
Sign up to set email alerts
|

Oligoaryl Cruciform Structures as Model Compounds for Coordination‐Induced Single‐Molecule Switches

Abstract: The synthesis of two new cruciform structures 3 and 4 comprising an oligo(phenylene-vinylene) (OPV) and a perpendicular oligoaryl bar -namely an oligophenylene (OP) (3) and a naphthyl-phenyl-naphthyl system (4) -is reported. The OPV rod consists of two terminal pyridine units, whereas the oligoaryl rod bears two terminal acetylsulfanyl groups as protected anchor groups. The OPV bar was assembled via a Horner-Wadsworth-Emmons reaction, which directly led to the desired E,E isomers. The perpendicular oligoaryl b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 82 publications
(113 reference statements)
1
23
0
Order By: Relevance
“…An in situ deprotection and reprotection procedure was chosen to avoid disulfide formation. [220] [221] Since an acetyl protection group is not stable under basic condition it was not suitable for the following Suzuki reaction and another transprotection step was done. The acetyl protecting group of 40 was deprotected to the free thiole 41 by hydrochloric acid which was generated in situ with methanol and acetyl chloride in dichloromethane.…”
Section: Synthesis and Characterization Of Sulfur Functionalized Azo mentioning
confidence: 99%
“…An in situ deprotection and reprotection procedure was chosen to avoid disulfide formation. [220] [221] Since an acetyl protection group is not stable under basic condition it was not suitable for the following Suzuki reaction and another transprotection step was done. The acetyl protecting group of 40 was deprotected to the free thiole 41 by hydrochloric acid which was generated in situ with methanol and acetyl chloride in dichloromethane.…”
Section: Synthesis and Characterization Of Sulfur Functionalized Azo mentioning
confidence: 99%
“…However, transport studies based on model compounds synthesized within this project revealed the electronically superior coupling via a terminal thiophenol compared to a terminal pyridine subunit, in spite of the shorter electrode-electrode distance in the later case. [10] The first generation of cruciforms consisted of a sulfur-functionalized oligophenylenevinylene (OPV) fixation bar and a transversal pyridine-functionalized oligophenyleneethynylene (OPE) bar (Fig. 2).…”
Section: Molecular Designmentioning
confidence: 99%
“…We proposed a new switching concept based on the interplay between the integrated molecule and the electrodes, designed and synthesized the required molecules and investigated their transport properties. [9,10] The hypothesized switching concept relies on a structure consisting of two rigid-rod type π-systems which cross each other resulting in a molecular cruciform. Both π-systems as bars of the cruciform differ in their electronic transparency and in their terminal anchor groups to the electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been exploiting this technique extensively over the past years to determine some of the basic mechanisms at stake in the formation of molecular junctions. [21][22][23][24][25][26][27][28][29] Some examples are provided in the next section.…”
Section: Contacting Strategiesmentioning
confidence: 99%